Development of a Web-Based Information System for Student Leave Permission at Dar Al-Raudhah Islamic Boarding School: ISO Quality Standards Analysis - Destiana, Bonita; Priyanto, Priyanto; Irfan, Rahmatul; Khamim, Muhammad Gus; Ridlo, Muhammad Yusuf; Iqbal, Muhammad (Elinvo (Electronics, Informatics, and Vocational Education), 2023)
Dar Al-Raudhah Entrepreneur, Islamic Boarding School, has adopted digital technology by upgrading hardware and software also investing in reliable internet infrastructure. However, this school still faces issues with students' leave permission process due to reliance on manual bookkeeping and Excel, which leads to potential errors. Based on those problems, this research aims to create a web-based student leave permission system called SIPERSAN. The SIPERSAN system was developed with a Waterfall development model, which includes requirements analysis, design, implementation, testing, and deployment. The database is managed with MySQL, and the system is developed using PHP with the Laravel framework. Based on testing results, SIPERSAN has met the ISO 25010 standard for the four aspects: functionality, performance efficiency, reliability, and usability. Regarding functionality, this system has a score of 0.964, indicating it is very eligible. It rates 90% on GTMetrix (Grade B) for performance efficiency with an average loaded time of 2.06 seconds, making it eligible. Regarding reliability, the system is rated as very eligible for success based on evaluations performed with WAPT software. Usability is rated at 75.33%, which is considered eligible. SIPERSAN also received a positive response from users, who felt impacts such as facilitating the processing of student permits, increasing efficiency in managing student permit data, minimizing data errors, and assisting in recording student permits that are organized and systematic.